PENGARUH KOMPETENSI DAN MOTIVASI INTRINSIK TERHADAP KINERJA DIMEDIASI KEPUASAN KERJA GURU SMP NEGERI KECAMATAN COMAL KABUPATEN PEMALANG - 1352020061, Suwarni; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study investigated the Competence Effects on Performance and Intrinsic Motivation Teacher job satisfaction Mediated of Junior High School Teacher Comal District of Pemalang. The specific objectives of the study is to examine and analyze how the Influence of Competence and Performance Intrinsic MotivationÂ for Teacher Junior High School in the District Pemalang Comal. The usefulness of this study describes and expands previous research on the Competence and Intrinsic Motivation Effect on Teacher Performance. The population in this study PNS teachers SMP Comal District of Pemalang totaling 132 people from 5 Junior High School. In this study used primary data obtained by questionnaire. This research was condutected by distributing questionnaires in the form of limited questioning respondents. The research method uses quantitative data and analysis to statistical program SPSS (Statistical Package for Social Science). The data analysis method used was linear regression to test the effect of mediation. The results showed that the competence of positive and significant impact on job satisfaction of teacher. Intrinsic motivation positive and significant impact on job satisfaction. Competence positive and significant impact on teacher performance. Intrinsic motivation does not affect the perfomance of teachers. Job satisfaction does not mediates the influence of competence on teacher perfomance. Job satisfaction mediates the influence of intrinsic motivation on teacher perfomance.Keywords: Competence, Intrinsic Motivation, Job Satisfaction and Mediation